Microvascular vasoregulatory dysfunction in African Americans - An enhanced opportunity for early prevention and treatment of atherosclerotic cardiovascular disease - Renee P. Bullock-Palmer; Panithaya Chareonthaitawee; Ervin Fox; Garth M. Beache (American Heart Journal Plus, 2024)
Atherosclerotic cardiovascular disease and its risk factors and precursors are a major driver of disparities in cardiovascular health. This review examines reported evidence that vascular endothelial dysfunction, and its manifestation as coronary microvascular dysfunction, underlies observed excess morbidity and mortality in African Americans. Advanced imaging insights that reveal patho-mechanisms, along with population evidence from the Jackson Heart Study, and the growing evidence emanating from national and international clinical trials and registries are presented. We examine a physiological framework that recognizes insulin-resistant cardiometabolic underpinnings of the conditions of the American Heart Associations' Life's Essential Eight construct of cardiovascular health as a unifying basis that affords early prevention. Mechanistic-based therapeutic approaches, can subsequently be implemented to interrupt progression to adverse outcomes employing layered, or personalized, treatment strategies of a well-defined set of conditions or diseases. Remaining knowledge gaps are acknowledged.